STUDI EVALUATIF MEDIA RELATIONS HUMAS KEMENAKERTRANS RI - Fauzi, Ridwan (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
In building a relationship with the mass media, it is important to pay attention to how the concept or design of media relations activity is carried out, to determine what to do. This study aims to determine how activities are ex- ecuted media relations PR RI Manpower in maintaining good relations with the media. This study uses the theory of Human Relations. Through the paradigm of constructivism, phenomenology study uses descriptive qualitative method to collect data through in-depth interviews, observation, and study of Librarianship and related docu- ments. Researchers found that PR RI Manpower has been quite good in conducting media relations although not all media relations activities can be ful lled.Â